2018
DOI: 10.1111/joa.12814
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of extracellular matrix molecules in human uterine tubes during the menstrual cycle: a histological and immunohistochemical analysis

Abstract: The uterine tube (UT) is an important and complex organ of the women's reproductive system. In general, the anatomy and basic histology of this organ are well-known. However, the composition and function of the extracellular matrix (ECM) of the UT is still poorly understood. The ECM is a complex supramolecular material produced by cells which is commonly restricted to the basement membrane and interstitial spaces. ECM molecules play not only a structural role, they are also important for cell growth, survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 73 publications
0
15
0
1
Order By: Relevance
“…In general, we found that all skin types had similar amounts of proteoglycans as determined by histochemistry, but our analysis of specific molecules revealed some interesting differences for biglycan, which was more abundantly expressed by foot skin. Biglycan is a small leucine-rich dermatan sulfate proteoglycan that plays an important role in the maintenance of the structural and functional integrity of connective tissues by regulating collagen and controlling tensile strength (Mizumoto et al 2017 ; Godoy-Guzman et al 2018 ). Therefore, the abundance of this extracellular matrix component in foot skin could contribute to its increased biomechanical properties allowing this kind of skin to withstand greater stress forces than other skin types (Swensson et al 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, we found that all skin types had similar amounts of proteoglycans as determined by histochemistry, but our analysis of specific molecules revealed some interesting differences for biglycan, which was more abundantly expressed by foot skin. Biglycan is a small leucine-rich dermatan sulfate proteoglycan that plays an important role in the maintenance of the structural and functional integrity of connective tissues by regulating collagen and controlling tensile strength (Mizumoto et al 2017 ; Godoy-Guzman et al 2018 ). Therefore, the abundance of this extracellular matrix component in foot skin could contribute to its increased biomechanical properties allowing this kind of skin to withstand greater stress forces than other skin types (Swensson et al 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to further fractionate peptide samples, for example using basic reversed phase liquid chromatography [22, 25], to identify proteins present in lower abundance in the insoluble ECM scaffold, such as growth factors or cytokines, to determine which of these factors could regulate the microenvironment. While a recent study of the ampullar region of the fallopian tube demonstrated minimal changes between the luteal and follicular phase for six ECM analytes [16], there remains the potential for patient-to-patient variability with respect to age and hormonal status (i.e., pre- vs. post-menopausal, hormonal interventions, and menstrual cycle stage). To clarify the impact of these variables on the matrisome, a larger bank of benign fallopian tube samples could be collected and analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…First, the ECM composition, or “matrisome”, of the benign fallopian tube has not been defined. A recent study characterized the changes in type I and III collagens and four proteoglycans in the follicular and luteal phases of the menstrual cycle [16]; however, this report focused on the ampullar region of the fallopian tube, where relatively few STICs have been observed [17]. Global proteomics of the human fallopian tube have been reported [18-21], but these methods are not able to differentiate intra- vs. extra-cellular components or characterize the insoluble matrisome in depth.…”
Section: Introductionmentioning
confidence: 99%
“…These collagen-rich bundles are arranged parallel to the skin surface and in between run the elastic fibers. Just like in other tissues [15], the 3D organization of collagens depend on the presence of certain proteoglycans, such as decorin and versican [5].…”
Section: Biology Of the Skinmentioning
confidence: 97%